ZILVERPASS Study: ZILVER PTX Stent vs Bypass Surgery in Femoropopliteal Lesions. (April 2020) - Bosiers, Marc; Setacci, Carlo; De Donato, Gianmarco; Torsello, Giovanni; Silveira, Pierre Galvagni; Deloose, Koen; Scheinert, Dierk; Veroux, Pierfrancesco; Hendriks, Jeroen; Maene, Lieven; Keirse, Koen; Navarro, Tulio; et al.
Purpose: To report the 12-month results of a multicenter, prospective, randomized controlled trial to determine if the ZILVER PTX paclitaxel-eluting stent was noninferior in terms of safety and efficacy compared with surgical bypass.Materials and Methods: This is a study in symptomatic TransAtlantic Inter-Society Consensus (TASC) C and D femoropopliteal lesions comparing endovascular ZILVER PTX stenting vs surgical bypass surgery using a prosthetic graft ( ClinicalTrials.gov identifier NCT01952457). Between October 2013 and July 2017, 220 patients (mean age 68.6±10.5 years; 159 men) were enrolled and randomized to the ZILVER PTX treatment group (113, 51.4%) or the bypass treatment group (107, 48.6%). Most of the lesions were occlusions (208, 94.5%); the mean lesion length was 247.1±69.3 mm. The primary outcome measure was primary patency at 12 months, defined as no evidence of binary restenosis or occlusion within the target lesion or bypass graft based on a duplex-derived peak systolic velocity ratio <2.4 and no clinically-driven target lesion revascularization (TLR) in endovascular cases or reintervention to restore flow in the bypass.Results: The estimated 12-month primary patency rate was 74.5% (95% CI 66.3% to 82.7%) for the ZILVER PTX group vs 72.5% (95% CI 63.7% to 81.3%) for the bypass arm (p=0.998). Freedom from TLR at 12 months was 80.9% (95% CI 73.3% to 88.5%) for the ZILVER PTX group vs 76.2% (95% CI 68.0% to 84.4%) for the bypass group (p=0.471). The 30-day complication rate was significantly lower in the ZILVER PTX group (4.4% vs 11.3%, p=0.004). Also, procedure time and hospital stay were significantly shorter in the ZILVER PTX group (p<0.001 for both).Conclusion: With noninferior patency results, a lower complication rate, and shorter procedures and hospital stays, paclitaxel-eluting stenting might become a recommended treatment for long TASC C and D femoropopliteal lesions.